Ultrasound delivery of Surface Enhanced InfraRed Absorption active gold-nanoprobes into fibroblast cells: a biological study via Synchrotron-based InfraRed microanalysis at single cell level - F. Domenici (Nature Portfolio, 2019)
Abstract Ultrasound (US) induced transient membrane permeabilisation has emerged as a hugely promising tool for the delivery of exogenous vectors through the cytoplasmic membrane, paving the way to the design of novel anticancer strategies by targeting functional nanomaterials to specific biological sites. An essential step towards this end is the detailed recognition of suitably marked nanoparticles in sonoporated cells and the investigation of the potential related biological effects. By taking advantage of Synchrotron Radiation Fourier Transform Infrared micro-spectroscopy (SR-microFTIR) in providing highly sensitive analysis at the single cell level, we studied the internalisation of a nanoprobe within fibroblasts (NIH-3T3) promoted by low-intensity US. To this aim we employed 20 nm gold nanoparticles conjugated with the IR marker 4-aminothiophenol. The significant Surface Enhanced Infrared Absorption provided by the nanoprobes, with an absorbance increase up to two orders of magnitude, allowed us to efficiently recognise their inclusion within cells. Notably, the selective and stable SR-microFTIR detection from single cells that have internalised the nanoprobe exhibited clear changes in both shape and intensity of the spectral profile, highlighting the occurrence of biological effects. Flow cytometry, immunofluorescence and murine cytokinesis-block micronucleus assays confirmed the presence of slight but significant cytotoxic and genotoxic events associated with the US-nanoprobe combined treatments. Our results can provide novel hints towards US and nanomedicine combined strategies for cell spectral imaging as well as drug delivery-based therapies.